This American Franchise: This American Life, public radio franchising and the cultural work of legitimating economic hybridity. (April 2016) - Patterson, Eleanor
This essay examines the historical formation of public radio program This American Life ( TAL ) into a media franchise whose production and extension into film, television, live performances, and podcast spinoffs represent an economic hybridity of both public and commercial production cultures. However, due to the value of highbrow intellectualism often articulated with public radio and its supposed separation from commercial media, TAL 's economic hybridity occurs within a specific public radio context that encourages TAL 's producers to legitimate their collaboration with profit-driven media producers. Thus, TAL 's producers attempt to reinforce TAL 's distinction from commercial media through discourses of cinematic allusion, fundraising, and outsiderism in order to retain the cultural capital of public radio across a range of textual extensions. This study of TAL reminds us that media franchising studies needs to account for the participation of public radio within media industries, as well as the cultural tensions and negotiations associated with economic hybridity.